Penetapan Kadar Vitamin E dalam Ekstrak n-Heksan Buah Kelapa Sawit (Elaeis guineensis Jacq) dan CPO (Crude Palm Oil) dengan Metode KCKT - Mustika Furi; Rahma Dona; Vincent Tristan (Fakultas Farmasi Universitas Pancasila, 2022)
Palm fruit (Elaeis guineensis Jacq) is a natural source of vitamin E (tocopherol). This study has determined vitamin E levels in n-hexane extracts of palm fruit (Elaeis guineensis Jacq) and CPO (Crude Palm Oil) using HPLC (High Performance Liquid Chromatography) method. The subject were palm fruit and CPO obtained from plantations and palm fruit mills PT X located in Kampar district, Riau. Extraction of palm fruit and CPO using ultrasonication and saponification method. Measurement using HPLC obtained optimum conditions using mobile phase acetonitrile: water (86:14), flow 1 mL/minute, UV-Vis detector at wavelength 284 nm and obtained retention time is 3,488 minutes. Determination of the calibration curve is obtained the regression equation y = 702,872x + 3273,26 and r2 = 0,9985. The result of the determination vitamin E levels in the palm fruit extract and CPO sequentially is (469,4008 ± 2,5879) µg/mg and for CPO is (262,5248 ± 6,3987) µg/mg.